MENINGKATKAN KEMAMPUAN KOSAKATA BERBAHASA PADA KOSAKATA BERBICARA ANAK DENGAN PENERAPAN METODE BERMAIN PERAN DI KELOMPOK A TK RESTU IBU KOTA DEPOK - Ditta Kristina Putri; Nika Sintesa (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
This research was conducted to determine the speaking vocabulary skills of early childhood using the group A role playing method at Restu Ibu Kindergarten. The purpose of this learning improvement research was to look at the speaking vocabulary abilities of early childhood using the group A role playing method at Restu Ibu Kindergarten. In this research activity, a classroom action research model was carried out collaboratively between teachers and colleagues in class A. This research involved 20 children in group A. The data collection process was carried out by researchers by collecting the results of documentation and observation with analytical techniques, namely in the form of descriptive quantitative. The tool used is an observation instrument sheet. There is a success target in this study, namely achieving 75% of the 20 children who have language vocabulary skills which are carried out in cycle 1 and cycle 2 which shows the achievement results in the Pre-action stage with a percentage of 25%, in Cycle 1 as much as 50%, and in Cycle 2 with a success percentage of 85%. This proves that the research carried out has achieved indicators of success in children's early language vocabulary skills that have been applied by researchers. Based on the results of the study which showed an increase of more than 85%, it can be concluded that the Role Playing method can improve vocabulary skills in children's speaking vocabulary by applying the role playing method in group A, Kindergarten, Restu, Ibu Depok.